INVESTIGASI PERAN FEE BASED INCOME TERHADAP PROFITABILITAS (ROA) DI BANK SYARIAH INDONESIA (Studi Kasus Pada PT. Bank Syariah Mandiri Periode 2005-2014) - Iqbal Rafiqi; Fatati Nuryana; Maftuhatul Faizah; Achmad Jufri (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2020)
The existence of fee-based income solutions and services shows Islamic banks' attempts to improve, one of which is PT. Bank Syariah Mandiri, which can generate a fee-based income of Rp. 783,649,000,000. (September 2014,) This is intrinsically tied to Islamic banks' approach to satisfy the company's goal of improving profits, and BI is more concerned with evaluating a company's profitability based on the amount of return on assets (ROA) than than return on equity (ROE) bank. At PT. Mandiri Syariah Bank, the goal of the study was to evaluate the increase of fee based income (FBI) and see if there was an influence of fee based income on the rate of return on assets. The statistical method of simple linear regression analysis is used in this research for quantitative analysis. The research data that has been collected was secondary data. The sample was collected from PT. Bank Syariah Mandiri's quarterly financial statements from 2005 to 2015, which can be accessed at www.bi.go.id. The results showed that hypothesis testing with t test and F test resulted in an independent variable, namely fee based income (FBI), having a significant effect on the level of return on assets (ROA). The t test test (Table Coefficients) obtained a t value of 4.444, - while statistical table (t table) obtained a t value of 2.032, - meaning ttable tcount (2. with t and F each having a significance value of 0.000, which is less than 0.05. Based on the results of the regression analysis, the regression equation obtained is Y = 0.714 + 0.0000008606 X, this equation states that in the absence of fee based income (FBI) the rate of return on assets (ROA) is 0.714, - and every increase of 1,000,000 rupiah fee based income (FBI) will cause an increase of 0.8606, - in the rate of return on assets (ROA). The coefficient of determination (R2) is 0.349, - (Ajusted R Square) this means that 35% of the variation in return on assets (ROA) is explained by variations in fee based income (FBI) while the remaining 65% is explained by variations in other factors such as income from Islamic bank financing.